The impact of agentic and communal exercise messages on individuals' exercise class attitudes, self-efficacy beliefs, and intention to attend - Howle, T.; Dimmock, J.; Ntoumanis, Nikos; Chatzisarantis, Nikos; Sparks, C.; Jackson, B. (Human Kinetics, 2017)
We tested the effects of advertisements about a fictitious exercise class-derived using the theoretical constructs of agency and communion-on recipients' perceptions about, and interest in, the class. The final sample consisted of 150 adults (M age = 44.69, SD = 15.83). Results revealed that participants who received a communal-oriented message reported significantly greater exercise task self-efficacy and more positive affective attitudes relative to those who received an agentic-oriented message. Communal (relative to agentic) messages were also indirectly responsible for greater intentions to attend the class, via more positive selfefficacy beliefs and affective attitudes. These findings were obtained despite the use of another manipulation to orient participants to either agency or communion goals. The results indicate that the primacy of communion over agency for message recipients may extend to exercise settings and may occur irrespective of whether participants are situationally oriented toward agency or communion.